Pola Hidup Anak Terang: Sebuah Tuntunan Hidup Menurut Efesus 5:7-11 - Firman Panjaitan (Predica Verbum: Jurnal Teologi dan Misi, 2024)
This study discusses the pattern of living as a child of light as revealed in Ephesians 5:7-11. This study is important, because today's phenomenon shows that many Christians do not live in self-control, and results in many Christians who have an unholy lifestyle. This unholy lifestyle will ultimately have a bad impact on the life of Christianity in general. This study uses qualitative methods with the approach of literature and textual-contextual interpretation. The results show that the pattern of living as a child of light in Ephesians 5:7-11, provides a picture of the values and morals of life that must be applied in the lives of believers today. Understanding the position of self as light in God encourages Christians not to do dark acts, because the light must produce goodness, justice and truth. Thus, the pattern of Christian life as children of light not only has an impact on the value of ethical life, but makes that life an example for the lives of others through the fruits of life produced by every Christian/believer.